2014
DOI: 10.1590/0004-2730000003413
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery – An update for the endocrinologist

Abstract: Obesity is a major public health problem, is associated with increased rates of mortality risk and of developing several comorbidities, and lessens life expectancy. Bariatric surgery is the most effective treatment for morbidly obese patients, reducing risk of developing new comorbidities, health care utilization and mortality. The establishment of centers of excellence with interdisciplinary staff in bariatric surgery has been reducing operative mortality in the course of time, improving surgical safety and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 48 publications
(89 reference statements)
0
24
0
5
Order By: Relevance
“…Overweight and obesity have significantly increased morbidity and mortality around the world due to its associated medical conditions (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity have significantly increased morbidity and mortality around the world due to its associated medical conditions (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some cardiovascular safety trials with diabetes medications have demonstrated that these drugs offer cardiovascular protection (2); more data on hard outcomes are required to better assess not only the efficacy, but mainly the safety in very large series before endorsing the widespread indication of bariatric surgery in the subpopulation of type 2 diabetics with a BMI below 35 kg/m 2 . A significant proportion of individuals undergoing bariatric surgery experiment weight regain, residual diabetes or diabetes relapse (i.e., around one third of initial remitters over five years do not achieve remission or have diabetes recurrence), requiring to cope with the residual diabetes and emerging obesity (2,3) and also to deal with lifelong nutritional deficiencies and other potential long-term complications, such as vomiting, adhesions, strictures, gallstones, hernias, drinking problems, and small-bowel obstruction (4,5). In the scope under discussion, it is essential that the diagnosis of diabetes in patients undergoing bariatric surgery be reliable and safe.…”
mentioning
confidence: 99%
“…In recent years, episodes of severe late postprandial hypoglycemia have been increasingly reported in gastric bypass patients. In the evaluation of these most frequently asymptomatic hypoglycemic events, fasting and post-prandial self-monitoring reflectance meter glucose determinations in the home setting, or fasting and post-prandial blood glucose concentration measurements can be requested occasionally and, if symptoms of hypoglycemia occur likewise (5,7,8). These patients could also be evaluated by ambulatory continuous measuring of interstitial fluid glucose systems (5,8) or a mixed meal test, preferably liquid (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations